COLOR THERAPY WITH CRYSTALS AND GEMSTONES - Gupta, Jyoti (International Journal of Research -GRANTHAALAYAH, 2014)
Gems are well-compressed small pieces found in mineral deposits found inside earth. Pearls and amber are notable exceptions in that they are formed from organic materials. Most of the gemstones are crystalline. A crystalline mineral is formed by a distinct 3-dimensional atom and this is a unique characteristic of gemstones. They possess color, hardness, aesthetic beauty, clarity and they can be cut to give sparkle.According to David Marcum’s remarks in his book “The Dow Jones Irwin Guide to Fine Gems and Jewelry”: